Enabling a Disaster‐Resilient Workforce: Attending to Individual Stress and Collective Trauma. Issue 6 (25th August 2017) - Raveis, Victoria H.; VanDevanter, Nancy; Kovner, Christine T.; Gershon, Robyn
Abstract: Purpose: Superstorm Sandy forced the evacuation and extended shutdown of New York University Langone Medical Center. This investigation explored how nurses were impacted by the disasters and how they can best be supported in their nursing responsibilities. Design: Sequential mixed methods were used to explore the psychosocial issues nurses experienced throughout the course of this natural disaster and its lingering aftermath. Methods: In‐depth interviews were conducted from April to June 2013 with a subsample of nurses who participated in the evacuation deployment ( n = 16). An anonymous, Internet‐based cross‐sectional survey sent to all registered nurses employed at the hospital at the time of the storm explored storm impact and recovery. Between July and September 2013, 528 surveys were completed. Findings: The qualitative data revealed challenges in balancing professional obligations and personal concerns. Accounts described dealing in the immediate recovery period with unexpected job changes and resultant work uncertainty. The storm's lingering aftermath did not signify restoration of their predisaster lifestyle for some, but necessitated coping with this massive storm's long‐lasting impact on their personal lives and communal loss. Conclusions: Nurses working under the rapidly changing, uncontrolled, and potentially dangerous circumstances of a weather‐related disaster are also experiencing concerns about their families' welfare and worries about personal loss. These multiple issues increase the psychosocial toll on nurses during a disaster response and impending recovery. Clinical Relevance: Awareness of concerns and competing demands nurses experience in a disaster and aftermath can inform education and services to enable nurses to perform their critical functions while minimizing risk to patients and themselves.